The Impact of Psychoanalytic Sessions on Reducing Psychological Stress Among Passport Department Employees in The Independent Zakho Administration - Arian Naamat (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2025)
This study aimed to investigate the impact of psychoanalytic sessions on reducing psychological stress among employees of the Passport Department in the Independent Zakho Administration. The study employed a quasi-experimental method based on a pre-test/post-test single-group design. The research sample consisted of 11 employees selected purposively based on specific inclusion criteria. The psychoanalytic intervention consisted of 15 daily sessions lasting 45 minutes each, conducted over three weeks from February 2 to February 20, 2025. Results showed statistically significant differences between pre-test and post-test measurements in favor of stress reduction, with very large effect sizes (?² = 0.894, d = 2.341) indicating the high effectiveness of psychoanalytic sessions in reducing workplace psychological stress among passport department employees.